2022
DOI: 10.1080/21655979.2021.2018974
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Long non-coding RNA muscleblind like splicing regulator 1 antisense RNA 1 (LncRNA MBNL1-AS1) promotes the progression of acute myocardial infarction by regulating the microRNA-132-3p/SRY-related high-mobility-group box 4 (SOX4) axis

Abstract: Long non-coding RNA muscleblind like splicing regulator 1 antisense RNA 1 (LncRNA MBNL1-AS1) exerts vital role in various physiological processes. However, its functions in acute myocardial infarction (AMI) are not elucidated. AMI model was constructed using Wistar rats and it was found that LncRNA MBNL1-AS1 was upregulated in AMI model according to the quantitative real-time polymerase chain reaction (qRT-PCR) results. The left ventricular systolic pressure (LVSP), left ventricular end diastolic pressure (LVE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…MBNL1-AS1 has been proven to repress cell proliferation and migration in these cancers. In addition, MBNL1-AS1 is reported to be upregulated in acute myocardial infarction, and silencing MBNL1-AS1 reduces myocardial injury in animal models [12]. From the current research results, we know that MBNL1-AS1 reduces cell survival in both cancer and noncancer cells.…”
Section: Introductionmentioning
confidence: 75%
“…MBNL1-AS1 has been proven to repress cell proliferation and migration in these cancers. In addition, MBNL1-AS1 is reported to be upregulated in acute myocardial infarction, and silencing MBNL1-AS1 reduces myocardial injury in animal models [12]. From the current research results, we know that MBNL1-AS1 reduces cell survival in both cancer and noncancer cells.…”
Section: Introductionmentioning
confidence: 75%
“…Overexpression of MBNL1-AS1 can inhibit tumorigenesis via miR-135a-5p/PHLPP2/FOXO1 axis [ 28 ]. MBNL1-AS1 also was reported that promoting the progression of acute myocardial infarction [ 29 ]. Gastric cancer (GC) has been identified as the most common malignant tumor for a long time.…”
Section: Discussionmentioning
confidence: 99%